1974
DOI: 10.1111/j.1365-2389.1974.tb01110.x
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐structural Differences Between Arable and Old Grassland Soils as Shown in the Scanning Electron Microscope

Abstract: Summary The scanning electron microscope has been used to compare the microstructure of an old grassland soil with that of an arable soil of the same soil series. The micrographs give more direct evidence than previously available of the presence of an adherent, presumably organic, matrix binding the clay and other particles of the old grassland soil. Fungal hyphae were also observed. Neither of these features was present to the same extent in the old arable soil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 3 publications
0
7
0
1
Order By: Relevance
“…It is believed that stabilization of aggregates by fungi in the field is limited to periods when readily decomposable material has been added to the soil in large amounts leading to a flush of hyphal growth (Martin et al, 1955;McGill et al, 1973;Low and Stuart, 1974). This may be true of the fungal species which most workers have studied.…”
Section: Temporary Binding Agentsmentioning
confidence: 99%
“…It is believed that stabilization of aggregates by fungi in the field is limited to periods when readily decomposable material has been added to the soil in large amounts leading to a flush of hyphal growth (Martin et al, 1955;McGill et al, 1973;Low and Stuart, 1974). This may be true of the fungal species which most workers have studied.…”
Section: Temporary Binding Agentsmentioning
confidence: 99%
“…Bailey et al (1973) noted that aggregation of loess by algae was enhanced by the presence of their associated bacteria and fungi. Gel'tser (1940) suggested that the decomposition of fungal hyphae yields products that are better aggregate stabilizers than those from most other sources, and Low and Stuart (1974) suggested that although neither roots nor fungal hyphae persist for long in soil, they may act as scaffolding from which the products of bacterial action could form transient binding agents. Several workers have observed bacteria in the amorphous material around fungal hyphae (Clough and Sutton, 1978;Tisdall and Oades, 1979).…”
Section: Interactions Between Groups Of Microorganisms or With Rootsmentioning
confidence: 99%
“…Our soil columns were collected in late May of 1998. Previous researchers also have shown that perennial vegetation can increase soil infiltration (Low and Stuart, 1974;Carter et al, 1994;Broersma et al, 1995) due to the presence of large number of root channels.…”
Section: Fate Of Atrazine In Rbs and Cropped Area Soilsmentioning
confidence: 94%